ANATOMY OF CAUSES AND EFFECTS OF THE FARMER-HERDER CONFLICT ON FOOD SECURITY IN BENUE STATE, 2015-2023 - ACHANYA JULIUS JOHN; VARZOA LUMA (International Studies Journal)
Benue State has recorded significant increase in farmer-herder conflict and major drawbacks in communal coexistence. This study examines the causes of the conflict and its effects on food security in the state. The structural conflict theory was used in analyzing the major variables while descriptive documentary design involving a mix of exploratory interview, Focus Group Discussion, observation, analyses of official documents and secondary data was utilized to triangulate evidence. Twenty (20) participants were purposively drawn from the population in the study area for interviews and focused group discussions and their responses were transcribed, presented and analyzed in a descriptive form using thematic headings. Deriving from the study findings, the results generated indicated that the underlying cause of the farmer-herder conflict in Benue State is climate change with its attendant consequence of herders migrating from the north to the state in search of pasture and water points. However, trigger causes muted by respondents include but not limited to illegal invasion of farms and destruction of crops by cattle, cattle rustling and theft; passage of the Open Grazing Prohibition and Ranches Establishment Law 2017, among others. Effects of the conflict on food security include the destruction of human lives and animals, farmlands and properties, drop in food production, hike in food prices, and rise in poverty level among the people, social dislocation and population displacement, among others. Against this backdrop, the study recommends that aside intensifying campaigns and actions against climate change, the Benue State Government and its critical stakeholders should strengthen and improve local peace building and reconciliation systems, among others.